Reliable and Autonomous Computational Science International Conference, RACS 2010, Atlanta, GA, USA, October 27-30, 2010 - Shin, Sung Y.; Gantenbein, Rex.; Kuo, Tei-Wei.; Hong, Jiman; SpringerLink (Online service) (Basel : Springer Basel, 2010)
Increasing size and complexity of software and hardware systems makes it harder to ensure their reliability. At the same time, the issues of autonomous computing become more critical as we more and more rely on software systems in our daily life. Such complexity is getting even more critical with the ubiquitous computing of embedded devices and other pervasive systems. These trends ask for techniques and tools for developing reliable and autonomous software which can support software engineers in their efforts. This book summarizes the state of the art of research in the diverse fields concerned, including novel designs, case studies and experimental as well as theoretical results.
Embedded & Computer Systems -- A Distributed Two-Version Multi-Granularity Locking Protocol for Multi-Controller Storage Systems -- A Medical Device Safety Supervision over Wireless -- A Novel Memory-Aware CPU Allocation Policy for Multicore NUMA Architecture -- Power-Aware EDZL Scheduling upon Identical Multiprocessor Platforms -- Thermalaware Register File based on Heat Transfer -- Analysis of Autonomous Bandwidth-Delay-Balancing Characteristic in the Decay Usage Scheduler -- A Reliable Nested Transaction Model with Extension of Real-Time Characteristics -- Network Computing & Security -- PDF: A Novel Probability-based Data Forwarding Scheme in Lossy Wireless Sensor Networks -- A New Green-Scheduling Approach to Maximize Wireless Multimedia Networking Lifetime via Packet and Path Diversity -- Design of a reliability enhancement scheme for the grid-topology mesh network -- A Reliable Watchdog Protocol with Two-way Mutual Confirmation in Wireless Multi-Hop Networks -- Energy Efficient Power Management for Multi-Mode Wireless Network Devices -- An Efficient and Reliable flooding in MANETs -- A Fast Agreement Protocol for Underwater Wireless Sensor Networks -- Autonomous traffic management for CDMA-based real-time services in in-building environments -- Protection against Buffer Overflow Attacks via Dynamic Binary Translation -- Applications -- XA2C Framework for XML Alteration/Adaptation -- An Automatic Method for WordNet Concept Enrichment using Wikipedia Titles -- Design of Interval Type-2 Fuzzy Set-based Fuzzy Neural Networks Using Successive Tuning Method -- Multimedia -- Improving Image Segmentation Algorithms with Differential Evolution -- TOF Camera based 3D Fingertip Location Estimation.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering